Seasonal Variations in Atmospheric Composition as Measured in Gale Crater, Mars. Issue 11 (21st November 2019) - Trainer, Melissa G.; Wong, Michael H.; McConnochie, Timothy H.; Franz, Heather B.; Atreya, Sushil K.; Conrad, Pamela G.; Lefèvre, Franck; Mahaffy, Paul R.; Malespin, Charles A.; Manning, Heidi L.K.; Martín‐Torres, Javier; Martínez, Germán M.; et al.
Abstract: The Sample Analysis at Mars (SAM) instrument onboard the Mars Science Laboratory Curiosity rover measures the chemical composition of major atmospheric species (CO2, N2, 40 Ar, O2, and CO) through a dedicated atmospheric inlet. We report here measurements of volume mixing ratios in Gale Crater using the SAM quadrupole mass spectrometer, obtained over a period of nearly 5 years (3 Mars years) from landing. The observation period spans the northern summer of MY 31 and solar longitude (LS ) of 175° through spring of MY 34, LS = 12°. This work expands upon prior reports of the mixing ratios measured by SAM QMS in the first 105 sols of the mission. The SAM QMS atmospheric measurements were taken periodically, with a cumulative coverage of four or five experiments per season on Mars. Major observations include the seasonal cycle of CO2, N2, and Ar, which lags approximately 20–40° of LS behind the pressure cycle driven by CO2 condensation and sublimation from the winter poles. This seasonal cycle indicates that transport occurs on faster timescales than mixing. The mixing ratio of O2 shows significant seasonal and interannual variability, suggesting an unknown atmospheric or surface process at work. The O2 measurements are compared to several parameters, including dust optical depth and trace CH4 measurements by Curiosity. We derive annual mean volume mixing ratios for the atmosphere in Gale Crater: CO2 = 0.951 (±0.003), N2 = 0.0259 (±0.0006), 40 Ar = 0.0194 (±0.0004), O2 = 1.61 (±0.09) x 10 ‐3, and CO = 5.8 (±0.8) x 10 ‐4 . Plain Language Summary: The atmosphere of Mars is made up of primarily carbon dioxide, and during the Martian year, the barometric pressure is known to cycle up and down substantially as this carbon dioxide freezes out and then is rereleased from polar caps. The Mars Science Laboratory Curiosity rover has now acquired atmospheric composition measurements at the ground over multiple years, capturing the variations in the major gases over several seasonal cycles for the first time. With the Sample Analysis at Mars instrument, the annual average composition in Gale Crater was measured as 95.1% carbon dioxide, 2.59% nitrogen, 1.94% argon, 0.161% oxygen, and 0.058% carbon monoxide. However, the abundances of some of these gases were observed to vary up to 40% throughout the year due to the seasonal cycle. Nitrogen and argon follow the pressure changes but with a delay, indicating that transport of the atmosphere from pole to pole occurs on faster timescales than mixing of the components. Oxygen has been observed to show significant seasonal and year‐to‐year variability, suggesting an unknown atmospheric or surface process at work. These data can be used to better understand how the surface and atmosphere interact as we search for signs of habitability. Key Points: First multiyear in situ measurements of the major components of the Mars atmosphere have been obtained by the MSL/SAM investigation Seasonal variation of CO2, N2, and Ar reveals differences in atmospheric transport and mixing timescales Oxygen varies seasonally and interannually, independently from Ar and N2, on timescales too fast to be explained by known chemistry